Paracetamol (acetaminophen) for chronic non‐cancer pain in children and adolescents - Cooper, Tess E (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the analgesic efficacy, and adverse events, of paracetamol (acetaminophen) used to treat chronic non‐cancer pain in children and adolescents aged between birth and 17 years, in any setting.